P-doped RuPd nanoparticles anchored on Y2Ru2-xPdxO7 pyrochlore oxide surface as oxygen evolution and reduction electrocatalysts for Zn-air battery - Lee, Geunhyeong (2024)
Metal-air battery technology is the most promising green technology. However, the sluggish kinetics of the oxygen evolution/reduction reaction (OER and ORR), which are key reactions in air cathode, must be improved. In this study, Pd substitution was introduced into Y2Ru2O7 pyrochlore oxides and the ratio of Pd was varied (YRPO-x). Then, P-doped RuPd nanoparticles were synthesized on Pd-substituted YRPO pyrochlore (YRPO/RuPd-P) by an in situ exsolution process to create bifunctional electrocatalysts facilitating both reactions. The uniquely designed YRPO/RuPd-P catalyst exhibited the OER overpotential and Tafel slope (Ej10 = 232 mV; Tafel slope = 37.1 mV/dec). Furthermore, YRPO/RuPd-P shows an E1/2 of 0.82 V, indicating superior ORR activity. This was further investigated by applying in a unit-cell battery system, which showed an outstanding power density (163 mW/cm2) and robust charge–discharge stability. This study proposes a novel design strategy for bifunctional electrocatalysts.